Retention P by Iron Oxide in Acid Sulphate Soil after Land Reclamation - WAHIDA ANNISA; B.H PURWANTO (Indonesian Center for Agriculture Land Resource Development, 2010)
Acid Sulphate Soil is a kind of soil with high pyrite (FeS2) content. Miss management in land reclamation of acid sulphate soil will cause pyrite oxidation that made the soil becomes very acid. Pyrite oxidation on acid sulphate soil will produce iron oxides such as goethite (α-FeOOH) and hematite (α-Fe2O3). Goethite and hematite have ability to bind the anions and cations in the soilsuch as phosphate which produces a complex surface binuclear with model of Fe-OP(O2)-O-Fe. On acid sulphate land because of its association with soil Fe and its solubility alteration during reduction and oxidation processes of land, P is a limiting factor. More iron oxide in the soil, more P is retentioned. Each m.mol Fe in soil will bind P as much as 0,17 m.mol P.